2022
DOI: 10.1101/2022.05.30.493970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HSPB5 disease-associated mutations have long-range effects on structure and dynamics through networks of quasi-ordered interactions

Abstract: Small heat shock proteins (sHSPs) are chaperones whose importance in protein homeostasis is exemplified by dozens of missense mutations associated with tissue-specific disease states. Despite decades of studies, the structure, dynamics, and mechanism of chaperone activity remain unclear. Here we show that the human sHSP HSPB5 distinguishes native lens protein γD-crystallin from damaged γD-crystallin even though the mutant/damaged client is folded. The disordered N-terminal region of HSPB5 (NTR) is essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 53 publications
(71 reference statements)
1
14
0
Order By: Relevance
“…A range of deuterium uptake was observed for homo-oligomeric assemblies of HSPB4 and HSPB5, with similar patterns of exchange to other reports ( SI Appendix , Figs. S12 and S13 ; HSPB1, 20 ; HSPB4, 15 ; and HSPB5 at pH 7.5, 11 ). CTR-derived peptides exchange very rapidly, ACD-derived peptides exchange slowly reflecting the stable β-sandwich structure, and peptides from the NTR have intermediate exchange rates.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…A range of deuterium uptake was observed for homo-oligomeric assemblies of HSPB4 and HSPB5, with similar patterns of exchange to other reports ( SI Appendix , Figs. S12 and S13 ; HSPB1, 20 ; HSPB4, 15 ; and HSPB5 at pH 7.5, 11 ). CTR-derived peptides exchange very rapidly, ACD-derived peptides exchange slowly reflecting the stable β-sandwich structure, and peptides from the NTR have intermediate exchange rates.…”
Section: Resultsmentioning
confidence: 96%
“…HSPB4 and HSPB5 are the two most highly related of the 10 human sHSPs, with highest sequence similarity within the structurally conserved ACD and highest sequence divergence within the disordered NTR and CTR. Based on previous studies that revealed that the NTR of HSPB5 is required for its chaperone activity against γD-W130E ( 11 ), chimeric constructs were created in which the NTRs of HSPB4 and HSPB5 were swapped(“N4-B5” has the NTR of HSPB4 swapped onto HSPB5, “N5-B4” is the alternate chimera; SI Appendix , Fig. S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations